2023
DOI: 10.1161/jaha.122.028032
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Socioeconomic Inequities in Access to Left Atrial Appendage Occlusion

Abstract: Background Inequitable access to high‐technology therapeutics may perpetuate inequities in care. We examined the characteristics of US hospitals that did and did not establish left atrial appendage occlusion (LAAO) programs, the patient populations those hospitals served, and the associations between zip code–level racial, ethnic, and socioeconomic composition and rates of LAAO among Medicare beneficiaries living within large metropolitan areas with LAAO programs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In this cohort of patients with AF, 30 1; Figure 1). In 2020, LAAO accounted for 9.32% of all patients receiving either LAAO or OACs.…”
Section: Study Populationmentioning
confidence: 84%
See 1 more Smart Citation
“…In this cohort of patients with AF, 30 1; Figure 1). In 2020, LAAO accounted for 9.32% of all patients receiving either LAAO or OACs.…”
Section: Study Populationmentioning
confidence: 84%
“…This is consistent with a recent study showing zip codes with a higher proportion of Black or Hispanic patients had lower LAAO rates. 30 Another study reported that non-White patients had worse outcomes following LAAO implantation. 31 One hypothesis underlying such differential outcomes is that LAAO for non-White patients is more likely to be performed at centers with lower volume and experience, [32][33][34][35][36] which warrants future investigation for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of Medicare fee-for-service claims (2016 to 2019) by Reddy and colleagues revealed that between 2016 and 2019, 97.4% of new LAAO programs opened in the US were in metropolitan areas. 7 The authors found that LAAO centers, as compared to non-LAAO centers, provided care to patients with higher median household incomes. After adjustment for socioeconomic markers, age, and clinical comorbidities, LAAO procedures were less likely to be performed in zip codes with higher proportions of Black and Hispanic patients.…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment for socioeconomic markers, age, and clinical comorbidities, LAAO procedures were less likely to be performed in zip codes with higher proportions of Black and Hispanic patients. 7 Another important consideration that affects the demographic composition of those who undergo LAAO procedures is that White patients have a higher risk of AF than other racial and ethnic groups. 4 However, this only explains some of the underrepresentation of racial and ethnic minority groups among LAAO patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In addition to AS, health inequity has been noted to influence outcomes in a wide range of medical conditions. [14][15][16][17] We hypothesised that race and ethnicity significantly impact AS diagnosis, management and outcomes within a universal healthcare system (Figure 1a). We conducted a retrospective study using longitudinal electronic health record (EHR) data from a tertiary UK hospital (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%